Enhancement of Antibacterial Activity from Chicken Head Protein Hydrolysate Using Dual-Enzyme Hydrolysis - Andiana, Pramudya; Syahdan, Moch. Geerhan Miraja; Utama, Arif Hendra; Kasri, Kasri; Al Awwaly, Khothibul Umam; Manab, Abdul (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
The chicken head is one of the by-products with a high protein content. Therefore, chicken heads can be used as raw materials to produce protein hydrolysates containing bioactive peptides that have biological activities, such as antibacterial, anti-inflammatory, and antioxidant activities. This research aimed to evaluate the use of the combined ratio of papain and bromelain enzymes to produce chicken head protein hydrolysate that has antibacterial activity. The research method used in this study was a laboratory experiment using a completely randomized design (CRD) with four treatments and five replications. Statistical significance was done using one-way analysis of variance (ANOVA) followed by Duncan’s multiple range test (DMRT). The inhibition zones of chicken head protein hydrolysate using a combination of papain enzymes against Lactobacillus casei, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Salmonella typhimurium were 1.72-2.68, 1.19-4.47, 0.93-1.45, 1.64-2.46, and 1.01-3.62 mm, respectively. The result showed that the highest antibacterial activities against Lactobacillus casei, Escherichia coli, and Staphylococcus aureus were in A1 (hydrolysis using papain 75% and bromelain 25%), the highest antibacterial activities against Pseudomonas aeruginosa was in A3 (hydrolysis using papain 25% and bromelain 75%), and the highest antibacterial activity against Salmonella typhimurium was in A2 (hydrolysis using papain 50% and bromelain 50%). However, all the hydrolysate didn’t exhibit antibacterial activity against Bacillus subtilis. Chicken head protein hydrolysate had the potential to be an antibacterial agent against pathogenic bacteria.